Heavy metal uptake by novel miscanthus seed-based hybrids cultivated in heavy metal contaminated soil = Pobieranie metali ciężkich przez nasienne genotypy miskanta uprawiane na glebie zanieczyszczonej metalami ciężkimi - Krzyżak, Jacek; Pogrzeba, Marta; Rusinowski, Szymon; Clifton-Brown, John; McCalmont, Jon Paul; Kiesel, Andreas; Mangold, Anja; Mos, Michal (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
When heavy metal contaminated soils are excluded from food production, biomass crops offer an alternative commercial opportunity. Perennial crops have potential for phytoremediation. Whilst the conditions at heavy metal contaminated sites are challenging, successful phytoremediation would bring significant economic and social benefits. Seed-based Miscanthus hybrids were tested alongside the commercial clone Miscanthus x giganteus on arable land, contaminated with Pb, Cd and Zn near Katowice.
Keywords: Miscanthus; seed based hybrids; heavy metals; phytoremediation; genotypy nasienne; metale ciężkie; fitoremediacja